2012
DOI: 10.1007/s10529-012-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of ginsenosides Re and Rg1 into ginsenosides Rg2 and Rh1 by recombinant β-glucosidase

Abstract: Ginsenosides Re and Rg1 were transformed by recombinant β-glucosidase (Bgp1) to ginsenosides Rg2 and Rh1, respectively. The bgp1 gene consists of 2,496 bp encoding 831 amino acids which have homology to the glycosyl hydrolase families 3 protein domain. Using 0.1 mg enzyme ml(-1) in 20 mM sodium phosphate buffer at 37°C and pH 7.0, the glucose moiety attached to the C-20 position of ginsenosides Re and Rg1, was removed: 1 mg ginsenoside Re ml(-1) was transformed into 0.83 mg Rg2 ml(-1) (100% molar conversion) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 13 publications
0
44
0
1
Order By: Relevance
“…strain QM49 was isolated. In addition, the near-neutral optimal pH and mild optimal temperature of BglQM are similar to those of other ginsenoside-hydrolyzing family 3 ␤-glucosidases from bacteria (23,32,56).…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…strain QM49 was isolated. In addition, the near-neutral optimal pH and mild optimal temperature of BglQM are similar to those of other ginsenoside-hydrolyzing family 3 ␤-glucosidases from bacteria (23,32,56).…”
Section: Resultsmentioning
confidence: 56%
“…The results, which are summarized in Table 3, showed that BglQM was maximally active against PNPGlc followed by ONPGlc but had little effect on various other PNP-and ONP-glycosides, with the exception of PNP-␣-L-arabinofuranoside and PNP-␤-D-fucopyranoside. The specific activity of BglQM against PNP-␣-L-arabinofuranoside is not seen in ginsenoside-transforming glycoside hydrolase family 3 members from Terrabacter ginsenosidimutans (23) and Microbacterium esteraromaticum (32). However, BglQM cannot hydrolyze the arabinofuranoside at the outer position of the C-20 of the ginsenoside Rc, perhaps due to structural differences between the molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations